The Genomes of Oryza sativa: A History of Duplications - Yu, Jun; Wang, Jun; Lin, Wei; Li, Songgang; Li, Heng; Zhou, Jun; Ni, Peixiang; Dong, Wei; Hu, Songnian; Zeng, Changqing; Zhang, Jianguo; Zhang, Yong; et al. (PLOS Biology, 2005)
Comparative genome sequencing of indica and japonica rice reveals that duplication of genes and genomic regions has played a major part in the evolution of grass genomes.